Предмет: Алгебра,
автор: НоВыЙ13
Упростите:
![sqrt{2+ sqrt{3} } - sqrt{2- sqrt{3} } sqrt{2+ sqrt{3} } - sqrt{2- sqrt{3} }](https://tex.z-dn.net/?f=+sqrt%7B2%2B+sqrt%7B3%7D+%7D+-++sqrt%7B2-+sqrt%7B3%7D+%7D+)
Варианты ответов:
A)
B)
C)
D)
Ответы
Автор ответа:
0
√((√(2+√3) - √(2-√3))²)=√(2+√3-2√((2+√3)(2-√3))+2-√3)=
=√(4-2√(4-3))=√(4-2)=√2)
Otvet: c)√2
=√(4-2√(4-3))=√(4-2)=√2)
Otvet: c)√2
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Биология,
автор: Аноним
Предмет: Алгебра,
автор: belkatya510400
Предмет: Химия,
автор: KatyaDrachuk03
Предмет: Алгебра,
автор: Аноним